Supporting Youth Employment through Vocational Training Programs in Nepal - Bhatta, Kushmakar (Journal of Training and Development, 2020)
The effect of globalization on human capital development is decisive. A country that lacks the means to compete in global market is often left behind. A key contributor in this regard is the knowledge, skills and positive attitude of the workforce. Education and skills therefore are the driving forces of social development and economic growth of any country. The first Sustainable Development Goal (SDG) is to end poverty in all forms by 2030 and for that there is major focus on education and productive employment. SDG-4 focuses on people's access to modern and quality education, which also indicates the need of vocational education and trainings. Similarly, the SDG-8 is to promote sustained economic growth, higher levels of productivity and technological innovation which indicated the need of TVET for productive employment and economic growth. Therefore, employment level of the working age group people, its composition and the growth in employment opportunities appeared as the critical indicator of the development process in any economy. The present paper attempts to highlight the positive effects that was contributed by the Vocational Education and Training (VET) programs in socio-economic development of large number of disadvantaged and unemployed population of Nepal. Primary data and information collected from the purposively sampled respondents- 405 VET graduates who after training are employed in their occupational sector. The study including field observation was conducted in 2016 to obtain qualitative information that helps to establish the relationship between vocational training and employment of the trained youth. The finding of this study revealed that VET plays positive role in employment and income growth. However, it concludes with the recommendation that the participants need post training support to become a functional VET and to get a sustainable and decent employment in the labor market.